Plant diversity and carbon stock in sacred groves of semi-arid areas of Cameroon: case study of Mandara Mountains - Kemeuze, VA; Mapongmetsem, PM; Sonwa, DJ; Fongnzossie, E; Nkongmeneck, BA (International Journal of Environment, 2015)
The Mandara Mountain eco-region is one of the most important mountain areas of Cameroon. It is often considered as a refuge for several plant and wildlife species. This area is fragile and vulnerable, and faces severe threats from land use change, unsustainable exploitation of natural resources, desertification and climate change. Recent studies in sacred groves portrayed these land use types as indigenous strategies which can help to address these environmental problems. Understanding the plant diversity and carbon storage of these land use types in Mandara Mountain can be a good step towards their sustainable management for the delivery of diverse ecosystem services. In this perspective, we established a total of 10 nested circular plots of 1257 m2 each, in the sacred grove of the Mouhour village in Mandara Mountain, and all trees and shrubs with average diameter at breast height (dbh) ≥ 2.5 cm were counted. Tree biomass was estimated on the basis of DBH and understory biomass using destructive method. A total of 182 woody plants were measured, belonging to 21 species, 18 genera and 12 families. The richest family is Combretaceae with 5 species, followed by Caesalpiniaceae and Mimosaceae (3 species each). The analysis of species diversity indexes shows a relative important biodiversity and the vegetation structure showed a high occurrence of small-diameter of plant species. Mean aboveground carbon stock of 31.13 ± 10.8 tC/ha was obtained in the study area. Isoberlinia doka showed the greatest carbon stock (5.7 tC/ha) followed by Boswellia dalzielii (3.9 tC/ha), Acacia senegal (3.5 tC/ha), Anogeissus leiocarpus (3.3 tC/ha) and Terminalia laxiflora (3.1 tC/ha). These results suggest that the sacred groves of Cameroon dry lands need to be taken into account in national environment protection policies as an alternative to respond to international agreements related to biodiversity conservation, combatting desertification and climate change. DOI: http://dx.doi.org/10.3126/ije.v4i2.12659 International Journal of Environment Vol.4(2) 2015: 308-318